Artificial intelligence annotated clinical-pathologic risk model to predict outcomes of advanced gastric cancer - Chen, Yan; Shou, Lin; Xia, Ying; Deng, Yanju; Li, Qianguo; Huang, Zhishuang; Li, Youlan; Li, Yanmei; Cai, Wenliang; Wang, Yueshan; Cheng, Yingying; Chen, Hongzhuan; et al. (Frontiers in Oncology, 2023)
Background: Gastric cancer (GC) with synchronous distant metastases indicates a dismal prognosis. The success in survival improvement mainly relies on our ability to predict the potential benefit of therapies. Our objective is to develop an artificial intelligence annotated clinical-pathologic risk model to predict its outcomes. Methods: In participants (n=47553) with GC of the surveillance, epidemiology, and end results program, we selected patients with distant metastases at first diagnosis, complete clinical-pathologic data and follow-up information. Patients were randomly divided into the training and test cohort at 7:3 ratio. 93 patients with advanced GC from six other cancer centers were collected as the external validation cohort. Multivariable analysis was used to identify the prognosis-related clinical-pathologic features. Then a survival prediction model was established and validated. Importantly, we provided explanations to the prediction with artificial intelligence SHAP (Shapley additive explanations) method. We also provide novel insights into treatment options. Results: Data from a total 2549 patients were included in model development and internal test (median age, 61 [53-69] years; 1725 [67.7%] male). Data from an additional 93 patients were collected as the external validation cohort (59 [48-66] years; 51 [54.8%] male). The clinical-pathologic model achieved a consistently high accuracy for predicting prognosis in the training (C-index: 0.705 [range, 0.690-0.720]), test (C-index: 0.737 [range, 0.717-0.757]), and external validation (C-index: 0.694 [range, 0.562-0.826]) cohorts. Shapley values indicated that undergoing surgery, chemotherapy, young, absence of lung metastases and well differentiated were the top 5 contributors to the high likelihood of survival. A combination of surgery and chemotherapy had the greatest benefit. However, aggressive treatment did not equate to a survival benefit. SHAP dependence plots demonstrated insightful nonlinear interactive associations among predictors in survival benefit prediction. For example, patients who were elderly, or poor differentiated, or presence of lung or bone metastases had a worse prognosis if they undergo surgery or chemotherapy, while patients with metastases to liver alone seemed to gain benefit from surgery and chemotherapy. Conclusion: In this large multicenter cohort study, we developed an artificial intelligence annotated clinical-pathologic risk model to predict outcomes of advanced GC. It could be used to discuss treatment options.